Harta sebagai Amanah dalam Akuntansi Syariah: Implikasi Konseptual terhadap Pengakuan, Pengukuran, dan Pengungkapan Nilai - Riski Fadilah; Muhammad Abrar; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
This study discusses assets as a trust in Islamic accounting and its implications for the recognition, measurement, and disclosure of asset values. In Islamic tradition, assets are not merely the property of individuals, but rather a trust that must be managed responsibly for the benefit of the community, so that Islamic accounting requires a different conceptual approach from conventional accounting. This study uses a descriptive qualitative approach with literature review and conceptual analysis, examining primary and secondary literature related to the principles of trust, ownership, and sharia reporting practices. The results of the study show that asset recognition must consider normative ownership and social functions, asset measurement needs to integrate financial dimensions and social benefits, while the disclosure of trust asset values is still low, as seen in waqf institutions, where only 2.08% publish financial reports. In conclusion, sharia accounting serves as an instrument of transparency and accountability that combines economic, ethical, and social values, so that assets can be managed fairly and responsibly in accordance with sharia principles.